Acoustic correlates of emphatic stress in Malayalam - M, Irfana; B, Rofina; N, Sreedevi (Journal of All India Institute of Speech and Hearing)
Stress is a perceived prominent function at syllable, word, or sentence level.Emphatic stress is to convey di erent intents by emphasizing di erent words in sentences; without changing the meaning. The acoustic correlates ofemphatic stress include increased fundamental frequency, amplitude, and durationvaryingaccording the structure of languages. As there are no reports on acoustic correlates of emphatic stress in Malayalam language, the present study was aimed to investigate the same in Malayalam. A total of 20 native adult speakers of Malayalam with equal number of males and females were selected for the study. The stimuli included 10two word phrases with adjective and verbs/ nouns. The subjects were asked to readthe phrases with and without stress on the adjectives marked in red colour. Recorded stimuli subjected to acoustic analysisto extract the fundamental frequency (f0), intensity (dB) and duration (msec) parameters from the adjective part of each of the phrases using Praat(Version 5.3.17) software. Statistical analysis revealed signi cant increase in word duration in stressed conditions.